Importance of diet in amphibian metamorphosis‐based studies designed to assess the risk of thyroid active substances. Issue 3 (22nd September 2022) - Fort, Douglas J.; Leopold, M. Annegaaike; Wolf, Jeffrey C.; Todhunter, Kevin J.; Weterings, Peter J. J. M.
Abstract: The present study evaluated the hypothesis that dietary quality used in historical studies may impact the effects of chemical stressors on premetamorphic development and metamorphosis due to suboptimal nutritional quality. A modified Amphibian Metamorphosis Assay (AMA) was performed in which Nieuwkoop and Faber (NF) Stage 47 tadpoles of Xenopus laevis were exposed for 32 days to iodide (I − )‐deficient FETAX solution supplemented with <0.025, 0.17, 0.52, 1.58, and 4.80 μg I − /L (measured concentrations 0.061, 0.220, 0.614, 1.65, and 4.73 μg I − /L) and fed a pureed Frog Brittle (FB) diet. An AMA guideline benchmark group (four replicates) exposed to dechlorinated tap water and fed standard Sera Micron Nature® (SMN) diet was evaluated concurrently. Developmental delay, observed as changes in stage distribution or median developmental stage, occurred in FB treatments with 0.061, 0.220, and 0.614 μg/L I −, respectively. Developmental rates and hind limb length of the 1.65 and 4.73 μg/L I − groups were similar to each other, but both treatments fell short of the developmental rate achieved by the SMN benchmark. Iodide supplementation also had no impact on nonthyroidal growth endpoints, which were markedly reduced in FB‐fed frogs compared with their SMN‐fed counterparts. All larvae that received the FB diet had mildly to severely hypoplastic/atrophic thyroids, a condition for which iodine supplementation had little if any ameliorative effect. Collectively, these results suggested that nutritional deficiencies in the FB diet negatively affected both growth and metamorphic development, the latter of which was only compensated to a limited extent by iodine supplementation. Abstract : The present study evaluated the hypothesis that dietary quality used in historical studies may impact the effects of chemical stressors on premetamorphic development and metamorphosis due to suboptimal nutritional quality. A modified AMA was performed in which NF Stage 47 tadpoles of Xenopus laevis were exposed for 32 days to iodide (I − ) deficient FETAX solution supplemented with I − at five different concentrations and fed a pureed FB diet. The results suggest that nutritional deficiencies (beyond iodine deficiency) in the FB diet negatively affected both growth and metamorphic development, the latter of which was only compensated to a limited extent by iodine supplementation.